2016
DOI: 10.1111/joop.12150
|View full text |Cite
|
Sign up to set email alerts
|

Investigating affective dispositions as moderators of relationships between weekend activities and recovery experiences

Abstract: Recovery experiences achieved during a weekend are presumed to be outcomes of weekend activities. However, results examining relationships between them are mixed. In line with models of differential stress responses, we posited that these differences may be accounted for by affective dispositions. We examined three-way interactions between weekend activities (low-effort and work-related) and both positive trait affect (PA) and negative trait affect (NA) on recovery experiences (psychological detachment, relaxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 71 publications
2
18
0
Order By: Relevance
“…Our study contributes to the existing study by identifying recovery experiences as a vital situational variable that can improve the effect of weekend activities. Much previous research has simply explained the degree of recovery as an outcome measure of weekend activities [17,23]. This study, however, expanded on the previous research by identifying the differences of weekend activities' effect for job stress depending on the level of recovery experiences.…”
Section: Theoretical Contributionsmentioning
confidence: 92%
See 3 more Smart Citations
“…Our study contributes to the existing study by identifying recovery experiences as a vital situational variable that can improve the effect of weekend activities. Much previous research has simply explained the degree of recovery as an outcome measure of weekend activities [17,23]. This study, however, expanded on the previous research by identifying the differences of weekend activities' effect for job stress depending on the level of recovery experiences.…”
Section: Theoretical Contributionsmentioning
confidence: 92%
“…Second, our study found the key mediating mechanism to explain how weekend activities promoted employees' psychological well-being. Several studies have examined how weekend or leisure activities influenced employees' attitude toward their job and life such as job stress, life satisfaction, and recovery experiences [17,22,33,47,48]; however, the relationships among weekend activities, job stress, and psychological well-being have been rarely investigated. In particular, by identifying the substantial mediating role of job stress, this study provides useful insights to understand the key mechanism of how weekend activities facilitate psychological well-being of employees.…”
Section: Theoretical Contributionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with previous US-based studies conducted across a range of professions, ATs in our study scored slightly lower in psychological detachment and control but slightly higher in mastery and relaxation than other workers. 14,[28][29][30][31] Collectively, our data indicated that ATs may be better able to engage in leisure or relaxation and learn or take on new challenges than they can psychologically distance themselves from work or display autonomy over their nonwork time. These data are consistent with previous reports 1,7,12 of ATs who perceived that they were constantly in work mode and had little control over their work schedules.…”
Section: Discussionmentioning
confidence: 73%